Comparing financial centers by using gross value added as main indicator - Alessia Ortner; Hans Geiger (Universität Zürich, Institut für schweizerisches Bankwesen, 2006)
This study contributes to the discussion on the measurement of financial sector output. It also serves as a lead-in to discussing possible causes of productivity changes in banking and insurance companies and other financial services providers. We demonstrate how the financial sector's net output and service production can be measured using aggregate financial statement data. We briefly examine current treatments of financial services in the national income accounts and introduce a conceptual framework for the construction of a financial firm's output measure consistent with the accounting approaches. Financial institutions in different countries do different things. While London, New York and Tokyo may be the primary places for certain products, other centers may be equally or more important for others. If one were looking for a metric for an one-dimensional ranking of financial centers by size value-added in financial services would be most appropriate. It can be compared from company to company and country to country. Therefore the concept of “value added” is adopted to circumvent some of the difficulties, like differences in accounting and reporting standards, in making comparisons between banks and insurance companies in different countries. Furthermore, we focus on the one hand on the competitiveness of the Swiss banking and insurance industry compared to international competitors and on the other hand we analyze in particular the banking and insurance industry in Switzerland over time considering the following dimensions: Contribution of the industry to national economy, respectively of the different groups to the industry. Productivity measures. Domestic gross value added and gross value added abroad. Outsourcing rate. Analyzis of the creation and distribution of gross value added. Other profitability and efficiency measures.
Keywords: 330; Finanzmarkt; Branchenentwicklung; Schweiz